Pemikiran Mulla Sadra tentang Al-Hikmah Al-Muta’aliyah dan Relevansinya dengan Pendidikan Islam - Gunawan, Agung (Tsamratul Fikri | Jurnal Studi Islam, 2019)
After the Peripatetic philosophy conflict (hikmah al-masysya'i) and illuminationalist philosophy (hikmah isyroqi), came a new philosophy school born in Persia, known as transcendental philosophy (Hikmah al-Muta'aliyah). The Hikmah al-Muta'aliyah was brought by Mulla Sadra, the synthesis of the previous second stream, and the illuminating philosophy of the Philosophy. In this case, Hikmah al-Muta'aliyah has given a new breakthrough, with the concept of ashalah al-wujud, wahdatul wujud, tasykik al-wujud wujud az-zihni, wahid laa yashduru minhu illa al-wahid and al-harakah al-jauhariyyah and also illustrated by the process of God's remission through the concept he wrote down. in his monumental work four trips to God namely; al-Hikmah al-Muta'aliyah fi al-Asfar al-‘Aqliyah al-Arba'ah. Al-Hikmah Muta'aliyah al-Sadra is a synthesis of intellectual illumination (isyroqi), punishment and rational evidence ('aql, burhan or istidlal) as well as religion and revelation. Sadra agrees that perfect knowledge is rational knowledge, combined with spiritual experience that can be obtained by those who follow the text of the Qur'an and al-Hadith. The source of knowledge is the text of the Qur’an, al-Hadith and the sayings of the imams and scholars combined with the experience of intuition and punishment. In accepting knowledge, the most appropriate method is that Kasf is supported by the reasons and interpretations of religious texts. Hikmah al-Muta'aliyah is considered the most important for Islamic philosophy, Islam which gives the highest philosophy, which is supported by Bayani, ‘Irfani and Burhani in his analysis.